Microbiome and Metabolomics Reveal the Effects of Different Feeding Systems on the Growth and Ruminal Development of Yaks - Huang, Chun; Ge, Fei; Yao, Xixi; Guo, Xian; Bao, Pengjia; Ma, Xiaoming; Wu, Xiaoyun; Chu, Min; Yan, Ping; Liang, Chunnian (Frontiers in Microbiology, 2021)
The yak(Bos grunniens), as a symbolic livestock species in the plateau region, the change of feeding system is of great significance to improve its growth performance. Here, we comprehensively compared the effects of different feeding systems on the growth performance and ruminal development of yaks, and to investigate the effects on the ruminal microorganisms and metabolites of yaks using the 16s rRNA gene sequencing and liquid chromatograph-mass spectrometer(LC-MS) technologies. We found that house feeding significantly improved the growth performance (such as average daily gain, net meat weight, etc.) and rumen development of the yaks when compared to traditional grazing feeding. At genus level, the abundance of Rikenellaceae RC9 Gut group, Christensenellaceae R-7 Group, Lachnospiraceae NK3A20 group, Ruminococcaceae UCG-014, and Prevotellaceae UCG-003 showed significant differences and were closely related to rumen development in the two distinct feeding systems. Also, metabolomics revealed that the change in the feeding system significantly affected the concentration and metabolic pathways of the related rumen metabolites. The metabolites with significant differences were significantly enriched in purine metabolism (such as xanthine, adenine, inosine, etc.), tyrosine metabolism (L-tyrosine, dopaquinone, etc.), phenylalanine metabolism (dihydro-3-caumaric acid, hippuric acid, etc.) and cAMP signaling pathway (Acetylcholine, (-)-epinephrine, etc.). Our studies not only scientifically support the house fattening feeding system for yaks, but also provides new insights into the composition and function of microbial communities and the relationship between rumen microorganisms and ruminal development, growth and development of yaks.